Crosstalk of Various Biomarkers That Might Provide Prompt Identification of Acute or Chronic Cardiorenal Syndromes - Tasić, Danijela (Cardiorenal Med, 2016)
INTRODUCTION: Pathophysiological interaction between the heart and kidneys represents the basis for clinical entities called cardiorenal syndromes. The purpose of the study was to assess the relations between acute and chronic cardiorenal syndromes and biomarkers [advanced oxidation protein products, brain natriuretic peptide, malondialdehyde, xanthine oxidoreductase (XOD), xanthine oxidase, xanthine dehydrogenase, interleukin 8, cystatin C, plasminogen activator inhibitor-1, high-sensitive troponin T, C-reactive protein and glomerular filtration rate, measured by the Modification of Diet in Renal Disease (MDRD) formula], to hypothesize biomarkers that might provide a prompt identification of acute or chronic cardiorenal syndromes, and to distinguish acute versus chronic types of these syndromes. METHODS: A total of 114 participants were enrolled in this study, i.e. 79 patients divided into subgroups of acute and chronic cardiorenal syndromes and 35 volunteers. RESULTS: Nonadjusted odds ratio (OR) showed that there was a significant risk for acute cardiorenal syndrome with increased XOD activity (p = 0.037), elevated cystatin C concentration (p = 0.038) and MDRD (p = 0.028). Multivariable adjusted OR, on the other hand, revealed that only glomerular filtration rate measured by the MDRD formula had a significance for acute cardiorenal syndrome (p = 0.046). Nonadjusted OR showed a significant risk for chronic cardiorenal syndrome only in elderly (p = 0.002). Multivariable adjusted OR exhibited that age was the only risk factor for chronic cardiorenal syndrome (p = 0.012). CONCLUSION: Cystatin C, glomerular filtration rate measured by the MDRD equation and XOD were independent risk factors for acute cardiorenal syndrome, while age remained an independent risk factor for chronic cardiorenal syndrome. When comparing ORs of evaluated parameters, the highest significance for acute cardiorenal syndrome was plasma concentration of cystatin C.